On the use of ion-crosslinked nanocellulose hydrogels for wound healing solutions: Physicochemical properties and application-oriented biocompatibility studies. (15th October 2017) - Basu, Alex; Lindh, Jonas; Ålander, Eva; Strømme, Maria; Ferraz, Natalia
Highlights: Ca 2+ -crosslinked nanocellulose self-standing hydrogels are proposed for wound healing applications. The hydrogels could maintain a suitable moist environment for different types of wounds according to water retention tests. The hydrogels present excellent biocompatibility towards dermal fibroblasts and blood-derived monocytes/macrophages. The hydrogels are non pro-inflammatory in terms of cytokine secretion and reactive oxygen species production. The potential of nanofibrillated cellulose hydrogels for the development of advanced wound healing dressings is highlighted. Abstract: Calcium ion-crosslinked nanofibrillated cellulose (NFC) hydrogels were investigated as potential materials for wound healing dressings. The physicochemical properties of the hydrogels were examined by rheology and water retention tests. Skin cells and monocytes were selected for application-oriented biocompatibility studies. The NFC hydrogels presented entangled fibrous networks and solid-like behavior. Water retention tests showed the material´s potential to maintain a suitable moist environment for different type of wounds. The hydrogels did not affect dermal fibroblasts monolayer cultures upon direct contact, as cell monolayers remained intact after application, incubation and removal of the materials. Inflammatory response studies with blood-derived mononuclear cells revealed the inert nature of the hydrogels in terms of cytokine secretion and reactive oxygen species production. Results highlight the great potential of ion-crosslinked NFC hydrogels for the development of advanced wound dressings, where further functionalization of the material could lead to improved properties towards the healing of specific wound types.